Corporate Accountability in Foreign Direct Investment (FDI): Ensuring Compliance with Human Rights Standards - P.K., Venkateswaran; Phillipose, Geni (Journal of Neonatal Surgery, 2025)
Foreign investment plays a crucial role in fostering domestic economic growth, particularly in developing countries like India. Multinational corporations (MNCs) serve as key drivers of globalization, integrating economies by facilitating capital inflow, technological advancements, and industrial expansion. The growth of foreign investment is intrinsically linked to the proliferation of MNCs, which, in turn, stimulate economic development in underdeveloped and emerging economies by providing essential resources such as machinery, technical expertise, and entrepreneurial skills. However, while foreign direct investment (FDI) contributes significantly to economic progress, it also raises concerns regarding corporate accountability, particularly in relation to human rights compliance. As FDI establishes long-term financial and operational control by foreign entities, ensuring adherence to ethical business practices and legal frameworks becomes imperative. Developing nations must strike a balance between attracting foreign capital and enforcing corporate responsibility to prevent labor exploitation, environmental degradation, and violations of local regulations. This study examines the role of corporate accountability in FDI, focusing on mechanisms that ensure compliance with human rights standards. It explores how regulatory frameworks, international legal principles, and corporate governance policies can safeguard economic growth while upholding ethical business practices. By analyzing case studies of foreign investments in India, this research aims to highlight the challenges and policy recommendations necessary for fostering responsible investment and sustainable development.